Design of a CNC system for bone tissue bioprinting (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2022)
Research in the area of bone tissue regeneration has seen significant growth, due to the need to treat bone defects of different types, looking for new options that allow the characterization of living and functional tissue, capable of promoting bone formation from implants designed with biocompatible materials. This article describes the components and the process by which an optimal mixture is obtained for the development of bone tissue cells based on calcium carbonate, hydrolyzed collagen, and acetic acid. The resulting mixture is subsequently used for 3D printing of tibia bone segments, each section undergoing a hemolysis test to determine the cytotoxicity levels of the material and the viability of the mixture used in the printed model.
Keywords: Biomaterials; 3D-printing; scaffold